Safety Profile of Recommended Vaccinations in Adolescents: Data from Surveillance of Adverse Events Following Immunization in Puglia (Italy), 2016–2020 - Antonio Di Lorenzo (MDPI AG, 2021)
Adolescence is a critical period for immunization, in which the adhesion rate to recommended vaccinations is often lower than desired. Since the safety of new vaccines is one of the most important factors determining vaccination hesitancy, post-marketing surveillance of adverse events following immunization (AEFIs) is recommended by the World Health Organization (WHO) to better understand the safety of these drugs. This report describes AEFIs notified in Puglia (Italy) after recommended vaccinations in adolescents aged 12 to 18 years in 2016–2020 to determine the safety profile of these products in a real-life scenario. This is a retrospective observational study. Data were gathered from the list of AEFIs notified in subjects between 12 and 18 years of age following administration of recommended vaccines in Puglia in 2016–2020. AEFIs were classified according to the WHO’s decisional algorithm, and causality assessment was carried out for serious AEFIs. From 2016 to 2020, 323,627 doses of vaccine were administered to adolescents in Puglia and 50 AEFIs were reported (reporting rate: 15.4 × 100,000 doses). Of these, 17 (34.0%) were classified as serious, and causality assessment identified 13 of them (76.5%) as vaccine related. The most common symptoms were local reactions, fever and neurological symptoms. No deaths were notified. The benefits of immunization in adolescents appear to be greater than the risk of AEFIs for all studied vaccines; in fact, AEFIs occur in less than 0.1‰ of patients and are generally mild and self-limiting.